High‐entropy alloy stabilized and activated Pt clusters for highly efficient electrocatalysis. Issue 2 (23rd March 2022) - Shi, Wenhui; Liu, Hanwen; Li, Zezhou; Li, Chenghang; Zhou, Jihan; Yuan, Yifei; Jiang, Feng; Fu, (Kelvin) Kun; Yao, Yonggang
Abstract: Although Pt and other noble metals are the state‐of‐the‐art catalysts for various energy conversion applications, their low reserve, high cost, and instability limit their large‐scale utilization. Herein, we report a hybrid catalysts design featuring noble metal clusters (e.g., Pt) uniformly dispersed and stabilized on high‐entropy alloy nanoparticles (HEA, e.g., FeCoNiCu), denoted as HEA@Pt, which is prepared via ultra‐fast shock synthesis (∼300 ms) for HEA alloying combined with Pt galvanic replacement for surface anchoring. In our design, the HEA core critically ensures high dispersity, stability, and tunability of the surface Pt clusters through high entropy stabilization and core‐shell interactions. As an example in the hydrogen evolution reaction, HEA@Pt achieved a significant mass activity of 235 A/gPt, which is 9.4, 3.6, and 1.9‐times higher compared to that of homogeneous FeCoNiCuPt (HEA‐Pt), Pt, and commercial Pt/C, respectively. We also demonstrated noble Ir stabilized on FeCoNiCrMn nanoparticles (HEA‐5@Ir), achieving excellent anodic oxygen evolution performance and highly efficient overall water splitting when combined with the cathodic HEA@Pt. Therefore, our work developed a general catalysts design strategies by using high entropy nanoparticles for effective dispersion, stabilization, and modulation of surface active sites, achieving a harmonious combination of high activity, stability, and low cost. Abstract : The hybrid high‐entropy design of HEA‐supported noble metal catalysts is promising for efficient dispersion, stabilization, and modulation of the surface‐active sites toward high activity, stability while being low cost.